Unexpected early loosening of rectangular straight femoral Zweymüller stems with an alumina-reduced surface after total hip arthroplasty—a prospective, double-blind, randomized controlled trial - Céline S. Moret; Salim El Masri; Benjamin L. Schelker; Niklaus F. Friederich; Michael T. Hirschmann (Journal of Orthopaedics and Traumatology, 2024)
Abstract Background Alumina particles from the grit blasting of Ti-alloy stems are suspected to contribute to aseptic loosening. An alumina-reduced stem surface was hypothesized to improve osseointegration and show comparable short-term outcomes to those of a standard stem. Methods In this prospective, double-blind, randomized trial, 26 standard (STD) and 27 experimental new technology (NT) stems were implanted. The latter were additionally treated by acid etching and ice blasting to remove alumina particles from the grit-blasting process. Follow-up occurred at 12 and 24 months. Bone mineral density (BMD) around the stem was measured by a dual-energy x-ray absorptiometry device (DEXA). Radiographs were reviewed for alterations. Clinical scoring comprised the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and the Harris Hip Score (HHS). Survival rates were calculated up to 50 months. Results Lower mean BMD and more severe cortical hypertrophies were found in the NT group. At 12 months, radiolucent lines were observed mostly in the metaphyseal zone for both groups, with a progression tendency in the NT group at 24 months. At 12 months, pain scores and the WOMAC total and physical activity scores were significantly lower in the NT group, without any differences thereafter. The number of NT stem revisions amounted to 6 (24%) and 11 (41%) at 24 and 50 months, respectively. Conclusion In the NT group, unexpected catastrophic failure rates of 41% caused by early aseptic loosening were noted within 50 months. Compared with the STD stems, NT stems lead to poor clinical and radiographic results. Level of evidence: II. Trial Registration: NCT05053048.